Energetics in competitive swimming and its application for training - Ogita, F. (Biomechanics and Medicine in Swimming X, 2006)
Competitive swimming events consist of different distances from 50m to 1500m. Since the exercise intensity and the relative irnportance of aerobic and anaerobic energy processes vary depending on the exercise time (and thus swimming distance), training regimen should be developed in accordance to time dependent metabolic profile. To understand the time dependent metabolic profile of arm stroke (A), leg kick (K) as well as whole body (S) swimming, the accumulated O2 uptake (AOU) and the accumulated O2 deficit (AOD) were determined at six different water flow. The AOU increased linearly with exercise time in all strokes, and the increased rate of AOU in A and K corresponded to 70, and 80% in S, respectively. The AOD in A and S significantly increased until 2-3min of exercise time, while the AOD in K more rapidly increased and the AOD at 30 s was not significantly different from those at 1 min and 2-3min. These results concerning time dependent metabolic profile in A, K, and S, would give a helpful Information to plan training successfully to improve the metabolic capacity for each stroke. Training effects of a moderate-intensity continuous training (CT) and a high-intensity intermittent training (IT), which are the most popular training regimens in competitive swimming, on VO2max and maximal accumulated O2 deficit (MAOD) were evaluated. After the training, VO2max increased significantly in both training modes. On the other hand, MAOD did not increase significantly in CT, but in IT. These results indicate that CT can improve only aerobic power but that adequate ET can improve both aerobic power and anaerobic capacity. Aerobic and anaerobic energy release in supramaximal swimming lasting 2-3 min were determined under different levels of hypobaric hypoxic condition. The exercise intensity (water flow rate) decreased with decrease in atmospheric pressure. During the exhaustive swimming, rate of aerobic energy release diminished with increase in hypobaric hypoxia, while not only AOD but also rate of anaerobic energy release throughout the exercise were unaffected despite the decreased O2 demand caused by diminished exercise intensity due to hypobaric hypoxia. Furthermore, the effects of high-intensity exercise training under a normal condition (C) and hypoxic conditions (H) on metabolic capacity were examined. After the training, VO2max significantly increased in both N and H, and no significant difference was observed in the increase ratio of VO2max between C and H. MAOD also significantly increased in both groups, however, the increase ratio of MAOD was significantly higher in H than C. The results suggest that the hypoxic training would be favorable for the improvement of the ability to supply anaerobic energy such as MAOD rather than VO2max.